World population prospects: The 1994 revision (United Nations, 1994)
This book presents the results of the United Nations 1994 Revision of the global population estimates and projections for the world, the more developed and less developed regions, least developed countries, six major areas and countries, 20 regions and 228 countries or areas. It is the practice of the Population Division in order to incorporate new data, new estimates and new analyses of data on population, fertility, mortality and international migration. THe numerical results are show in tabular form in annexes I-III to this book. Annex I, presents the results arraged by demographic indicator, such as population size and growth or crude birth rate, for all major areas, regions and countries. Annex II presents the agregated results arranged by major areas, region or special group. Annex III presents the results for each country or area